Effectiveness of Durian Seed Extract (Durio zibethinus Murr) on Blood Sugar Levels and Pancreatic Histopathology in Streptozotocin-Induced Wistar Rats - Valencia Angelina Halim; Tan Suyono; Linda Chiuman; Andika Z Tambunan; Felanda A Nadia (Jurnal Penelitian Pendidikan IPA, 2024)
Diabetes mellitus is a global health problem with a growing prevalence. Blood glucose levels that remain high can cause damage to various body tissues. including the pancreas. Durian seeds contain bioactive compounds such as alkaloids. triterpenoids. phenolics. and flavonoids that can reduce blood sugar levels. This study is an experimental study with a posttest only controlled group design conducted at the Pharmacology Laboratory of the Faculty of Pharmacy. University of North Sumatra and the Anatomical Pathology Laboratory of the Royal Prima Medan Hospital for more than 3 months. From the results of this study. durian fruit seed extract (Durio zibethinus Murr) in the phytochemical compound test contained alkaloids. saponins. flavonoids. and glycosides. With doses of 150 mg. 300 mg. and 450 mg proven to reduce blood sugar levels (KGD) in streptozotocin-induced Wistar rats. The highest dose in reducing blood sugar levels (KGD) with a dose of 450 mg. The group with a dose of 300 mg showed the best results in increasing the diameter of the islets of Langerhans.